On the feeding ecology of Pelophylax saharicus (Boulenger 1913) from Morocco - Zaida Ortega; Valentín Pérez-Mellado; Pilar Navarro; Javier Lluch (Acta Herpetologica, 2016)
The Sahara frog is the most common amphibian found in North Africa. However, the knowledge of its natural history is rather fragmentary. In the present work we studied the trophic ecology of Pelophylax saharicus at some areas of Morocco through the analysis of 130 gastric contents. We did not find any significant sexual dimorphism in body size of adult individuals. Consumed prey show similar sizes in both sexes, while bigger frogs normally eat larger prey. As in other Palearctic frogs, the diet is basically insectivorous, including terrestrial and aquatic prey. We found some differences in the diet of juveniles, with a higher proportion of flying prey, probably indicating a foraging strategy closer to ambush hunting. In the Atlas region, the high consumption of slow-moving terrestrial prey, as Gastropoda, stands out. Only in the Atlas region, the diet was similar to that described from other areas of North Africa, as Tunisia.